SCOPING REVIEW ON RISK FACTORS ASSOCIATED WITH HYPERTENSION IN INDONESIA - Hulu, Victor Trismanjaya; Saragih, Julwansa; S, Buenita; Damanik, Derma Wani; Zebua, Arianus; Yunia, Eva Anita; Rifai, Achmad; Dewi, Rani Sartika (Jurnal Ilmiah Keperawatan, 2025)
Background: Hypertension is a global health problem that contributes significantly to deaths from cardiovascular disease. Unhealthy lifestyles, including excessive salt consumption, physical inactivity, and obesity, are the primary factors. Without management, hypertension can lead to serious complications such as heart disease, stroke, and kidney failure. Objective: This study aims to investigate, summarise, and identify various scientific evidence related to hypertension risk factors. Methods: This study employed a scoping review approach organised according to the PRISMA protocol. The Population– Concept–Context (PCC) framework was utilised as an initial guideline in formulating research questions and searching for relevant articles. The literature search process was conducted using several databases, including Google Scholar and Scopus. The included articles had to meet the inclusion criteria, which were limited to open-access journals published between 2020 and 2025. From a total of 512 articles found, only 14 met the selection criteria and were suitable for analysis. The data extraction process was conducted by eight people on the 14 selected articles, followed by qualitative data analysis. Results: The findings indicate that factors such as age, gender, length of employment, consumption of salt, sugary drinks, high-fat foods, elevated total cholesterol levels, low vegetable intake, lack of physical activity, stress, and abdominal circumference that exceeds the recommended play a role in increasing the risk of hypertension. Conclusion: These factors trigger fluid retention, insulin resistance, dyslipidemia, and central obesity that together raise blood pressure and accelerate vascular damage.